The Influence of Product Innovation and E-Commerce on Competitive Advantage (Survey on Consumers of Compass Shoe Products) - Yusuf Muharam; Arga Sutrina; Ari Arisman (Journal of Indonesian Management, 2024)
The objectives of this research were to find out and analyze the innovation product, E-Commerce, and competitive advantage of Compass shoes, and the influence of the innovation product and E-Commerce competitive advantage on Compass shoes. The research method used in this research is survey methods, data used in this research are primary and secondary data. The object of this research was consumers of Compass shoes, using an accidental sampling method. The analysis technique used Multiple Regression Analysis. The results proved that an innovative product and E-Commerce influence the competitive advantage of Compass shoes.